A lithium-phobic-lithiophilic 3D gradient current collector and its preparation and application

By using lithium-eating-lithium-eating 3D gradient current collector in metal lithium secondary batteries, the problems of lithium dendrites growth and electrode/electrolyte interface instability are solved, and directional deposition of metal lithium and extended battery life are achieved.

CN116053482BActive Publication Date: 2025-04-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111267662.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-28
Publication Date
2025-04-11
Estimated Expiration
2041-10-28

AI Technical Summary

Technical Problem

During the charging and discharging cycle, metal lithium secondary batteries are prone to safety problems caused by lithium dendrites and unstable electrode/electrolyte interfaces, resulting in a shortened battery life and reduced capacity.

Method used

A lithium-agent-lithium-philic 3D gradient current collector is used to form a gradient structure by loading a lithium-agent organic layer and a lithium-agent metal layer on the 3D conductive framework to inhibit dendrite growth and improve interface stability.

Benefits of technology

Directional deposition of metal lithium is achieved, dendrites are inhibited, the safety and cycle stability of the battery are improved, and the life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116053482B_ABST
    Figure CN116053482B_ABST
Patent Text Reader

Abstract

The present invention relates to a 3D gradient current collector for lithium metal negative electrode and its preparation and application, with porous conductive material as 3D conductive skeleton, organic matter as upper layer, and lithium-philic metal as lower layer, the upper layer is prepared by molecular layer deposition, and the lower layer is prepared by sputtering; the prepared lithium-hating-lithium-philic 3D gradient current collector has high surface area and large lithium storage space, which is conducive to reducing the actual current density of lithium deposition and avoiding lithium dendrites from piercing the diaphragm; on the other hand, the introduction of the upper lithium-hating material is conducive to suppressing the uneven deposition of lithium metal, and the introduction of the lower lithium-philic material can realize the directional deposition of lithium metal and enhance the deposition uniformity. The 3D current collector is used for the negative electrode current collector of lithium metal battery, and through the synergistic effect of the above two aspects, the cycle stability of lithium metal negative electrode and the safety performance of battery can be greatly improved, and it has important practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium secondary batteries, and in particular relates to a current collector technology for lithium secondary batteries. Background Art

[0002] With the rapid development of economy, people's energy consumption is increasing, and non-renewable resources are decreasing, which makes the battery field receive more and more attention. With the rapid development of electric vehicles and portable devices, the existing lithium-ion batteries can no longer meet people's demand for higher energy density. Therefore, scientific researchers have shifted their research focus to lithium metal secondary batteries. The high specific capacity (3860mAh / g) and low reduction potential (-3.04V vs SHE) of lithium metal make it the most promising negative electrode material for lithium metal secondary batteries. In lithium metal secondary batteries, the lithium negative electrode is the main factor affecting the electrochemical performance of the battery, so the research on the lithium negative electrode is crucial.

[0003] However, there are still two problems that need to be solved for metal lithium negative electrodes. One is lithium dendrites. That is, the growth of lithium dendrites during the charge and discharge cycle of the battery will cause internal short circuits and serious safety problems in the battery. Another problem is the instability of the electrode / electrolyte interface. The repeated destruction and repair of the electrode / electrolyte interface layer (SEI) during the charge and discharge process will consume metal lithium and shorten the battery life; the generation of irreversible "dead lithium" will also reduce the capacity of lithium metal batteries.

[0004] 3D current collectors have a high specific surface area and a large pore volume, which is conducive to reducing the actual surface current density, alleviating the volume expansion during lithium deposition, and alleviating the safety problems caused by dendrites piercing the diaphragm. However, a single 3D current collector cannot achieve directional deposition of lithium metal, so lithium is easily deposited on the surface of the 3D current collector during high current density charging and discharging, and cannot effectively inhibit dendrites from piercing the diaphragm, causing serious safety hazards. Summary of the invention

[0005] In view of the above technical problems, the present invention proposes a lithium-phobic-lithium-philic 3D gradient current collector with good application effect in metal lithium batteries.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A 3D gradient current collector for a negative electrode of a lithium metal battery, the lithium metal battery comprising a diaphragm, the current collector comprising a 3D conductive skeleton, the 3D conductive skeleton being a porous conductive material; one side of the 3D conductive skeleton is loaded with a lithium-phobic organic layer, and the other side thereof is loaded with a lithium-philic metal layer; wherein the side of the current collector loaded with the lithium-phobic organic layer faces the diaphragm of the battery; the thickness of the organic layer is 10-100 nm, and the thickness of the lithium-philic metal layer is 30-150 nm.

[0008] Based on the above scheme, preferably, the porous conductive material is one or more of foam iron, foam nickel, foam copper, carbon felt, carbon cloth, and carbon paper; the organic layer material is one or more of polyimide, polyurea, polyamide (nylon 66), polyimide-amide, polyurethane, polythiourea, polyester, and polyethylene glycol; the lithium-philic metal layer material is one or more of gold, silver, platinum, and indium.

[0009] Based on the above solution, preferably, the porous conductive material has a thickness of 10-100 μm and a porosity of 50-95%.

[0010] Based on the above scheme, preferably, the lithium-phobic organic layer is prepared by molecular layer deposition, and the lithium-philic metal layer is prepared by sputtering.

[0011] Based on the above scheme, preferably, the method for preparing the lithium-phobic-lithiophilic 3D gradient current collector comprises the following steps:

[0012] (1) placing a porous conductive material in a molecular layer deposition (MLD) reactor, controlling the reaction temperature and time, and depositing a lithium-phobic organic layer on one side of the porous conductive material;

[0013] (2) placing the porous conductive material after the organic layer is deposited in a sputtering chamber, controlling the sputtering time, and depositing a lithium-philic metal layer on the other side opposite to the lithium-phobic organic layer to obtain the current collector;

[0014] The above steps (1) and (2) are performed in no particular order.

[0015] Based on the above scheme, preferably, the MLD reaction temperature is controlled to be 300-500° C., the reaction time is controlled to be 10-50 min, and the sputtering control time is 20-200 s.

[0016] The lithium-phobic-lithiophilic 3D gradient current collector is applied to lithium metal batteries.

[0017] The beneficial effects of the present invention are:

[0018] (1) The lithium-philic metal substrate of the 3D gradient current collector of the present invention can induce the nucleation of metallic lithium and achieve directional deposition of metallic lithium.

[0019] (2) The organic layer of the 3D gradient current collector of the present invention can inhibit the growth of dendrites and effectively alleviate the safety hazard caused by lithium dendrites piercing the diaphragm.

[0020] (3) The thickness of the layer prepared by the MLD and sputtering method in the present invention is controllable and the distribution is more uniform.

[0021] (4) The 3D gradient current collector prepared by the present invention can still maintain good metal lithium negative electrode stability under high rate charge and discharge conditions, has a low deposition and dissolution overpotential, fast surface reaction, and can achieve uniform deposition of lithium metal. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 : The lithium-phobic-lithium-philic 3D gradient current collector prepared in Example 1.

[0023] Figure 2 : Comparative Example 2 and Example 4, using different current collectors, the cycle performance of LiFePO4|Li battery.

[0024] Figure 3 : Comparative Example 2 and Examples 2, 4, and 6, using different current collectors, the rate performance of LiFePO4|Li batteries.

[0025] Figure 4 : Lithium deposition morphology of Comparative Example 1 (Figure a) and Example 1 (Figure b). DETAILED DESCRIPTION

[0026] The present invention is further described below by way of examples and comparative examples, but is not intended to limit the present invention.

[0027] Comparative Example 1

[0028] A commercial 8μm copper foil with a diameter of 19mm was used and 5mAh metal lithium was pre-deposited, Celgard 2325 was used as a separator, 1mol / L LiPF6 EC+DMC (volume ratio of 1:1) solution was used as an electrolyte, and lithium metal was assembled into a lithium|current collector battery. 2 At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0029] Comparative Example 2

[0030] Weigh 0.2g of commercial LiFePO4 powder and 0.025g of commercial Super P dispersed in 1g of N-methylpyrrolidone (NMP), stirred for 1h, added 0.25g of 10wt% polyvinylidene fluoride (PVDF) solution, the solvent is NMP, stirred for 5h, adjusted the scraper to 80μm, and coated on an aluminum film. After drying at 70℃ overnight, cut into small discs with a diameter of 14mm, weighed, and vacuum dried at 60℃ for 24h, the small discs coated with the synthesized carbon material were used as the positive electrode (the single-chip active material loading is about 1.5mgcm -2), in Comparative Example 1, the copper foil with pre-deposited lithium (5 mAh) was used as the negative electrode, celgard 2325 was used as the separator, and a solution of 1 mol / L LiPF6 in EC+DMC (volume ratio of 1:1) was used as the electrolyte to assemble a CR2016 button cell, and the cycle performance charge and discharge test was carried out at a rate of 0.5C.

[0031] Comparative Example 3

[0032] A 50μm nickel foam with a diameter of 19mm and 5mAh lithium metal deposited in advance was used, celgard 2325 was used as a separator, 1mol / L LiPF6 EC+DMC (volume ratio of 1:1) solution was used as an electrolyte, and lithium metal was assembled into a lithium|current collector battery. 2 At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0033] Comparative Example 4

[0034] The nickel foam (porosity of 80%, thickness of 50 μm) was placed in the sputtering chamber, the sputtering target was a gold target, and the sputtering time was 30 s; a lower lithium-philic gold layer was obtained with a thickness of 30 nm, and a 3D lithium-philic current collector was obtained.

[0035] The prepared 3D lithium-philic current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the lithium-philic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. 2 At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0036] Comparative Example 5

[0037] The nickel foam (porosity of 80%, thickness of 50 μm) was placed in an MLD reactor, the reaction temperature was 400°C, the reaction time was 20 min, and an upper organic layer with a thickness of 40 nm was obtained. The material of the organic layer was polyethylene glycol, and a 3D lithium-phobic current collector was obtained.

[0038] The prepared 3D lithium-phobic current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the non-lithium-phobic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. 2 At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0039] Comparative Example 6

[0040] Place nickel foam (porosity 80%, thickness 50μm) in an MLD reactor, the reaction temperature is 400°C, the reaction time is 2.5min, and an upper organic layer with a thickness of 5nm is obtained. The material of the organic layer is polyethylene glycol; place the above precursor in a sputtering chamber, the sputtering target is a gold target, the sputtering time is 80s, and a lower lithium-philic gold layer with a thickness of 80nm is obtained.

[0041] The prepared 3D lithium-philic current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the lithium-philic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. 2 At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0042] Comparative Example 7

[0043] Place nickel foam (porosity 80%, thickness 50μm) in an MLD reactor, the reaction temperature is 400°C, the reaction time is 5min, and an upper organic layer with a thickness of 10nm is obtained. The material of the organic layer is polyethylene glycol; place the above precursor in a sputtering chamber, the sputtering target is a gold target, the sputtering time is 200s, and a lower lithium-philic gold layer with a thickness of 200nm is obtained.

[0044] The prepared 3D lithium-philic current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the lithium-philic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. The deposition-dissolution cycle was carried out at a current density of 1 mA / cm2 and 1 mAh / cm2.

[0045] Comparative Example 8

[0046] Place nickel foam (porosity 80%, thickness 50μm) in an MLD reactor, the reaction temperature is 400°C, the reaction time is 100min, and an upper organic layer with a thickness of 200nm is obtained. The material of the organic layer is polyethylene glycol; place the above precursor in a sputtering chamber, the sputtering target is a gold target, the sputtering time is 10s, and a lower lithium-philic gold layer with a thickness of 10nm is obtained.

[0047] The prepared 3D lithium-philic current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the lithium-philic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. The deposition-dissolution cycle was carried out at a current density of 1 mA / cm2 and 1 mAh / cm2.

[0048] Example 1

[0049] Place nickel foam (porosity 80%, thickness 50μm) in an MLD reactor, the reaction temperature is 400℃, the reaction time is 20min, and an upper organic layer with a thickness of 40nm is obtained. The material of the organic layer is polyethylene glycol; place the above precursor in a sputtering chamber, the sputtering target is a gold target, and the sputtering time is 30s; obtain a lower lithium-philic gold layer with a thickness of 30nm, and obtain a 3D gradient current collector.

[0050] The prepared 3D gradient current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the lithium-philic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. 2 At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0051] Example 2

[0052] The LiFePO4 positive electrode was prepared by the method of Comparative Example 2, the 3D gradient current collector with pre-deposited lithium (5 mAh) in Example 1 was used as the negative electrode, celgard 2325 was used as the separator, and a 1 mol / L LiPF6 EC+DMC (volume ratio of 1:1) solution was used as the electrolyte to assemble a CR2016 button cell, and the cycle performance charge and discharge test was carried out at a rate of 0.5C.

[0053] Example 3

[0054] Place nickel foam (porosity 80%, thickness 50 μm) in an MLD reactor, the reaction temperature is 400°C, the reaction time is 40 min, and an upper organic layer with a thickness of 80 nm is obtained. The material of the organic layer is polyethylene glycol; place the above precursor in a sputtering chamber, the sputtering target is a gold target, the sputtering time is 30 s, and a lower lithium-philic gold layer with a thickness of 30 nm is obtained to obtain a 3D gradient current collector.

[0055] The prepared 3D gradient current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the lithium-philic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. 2 At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0056] Example 4

[0057] The LiFePO4 positive electrode was prepared by the method of Comparative Example 2, the 3D gradient current collector with pre-deposited lithium (5 mAh) in Example 3 was used as the negative electrode, celgard 2325 was used as the separator, and a 1 mol / L LiPF6 EC+DMC (volume ratio of 1:1) solution was used as the electrolyte to assemble a CR2016 button cell, and the cycle performance charge and discharge test was carried out at a rate of 0.5C.

[0058] Example 5

[0059] Place nickel foam (porosity 80%, thickness 50μm) in an MLD reactor, the reaction temperature is 400°C, the reaction time is 40min, and an upper organic layer with a thickness of 80nm is obtained, and the material of the organic layer is polyethylene glycol; place the above precursor in a sputtering chamber, the sputtering target is a gold target, the sputtering time is 60s, and a lower lithium-philic gold layer with a thickness of 60nm is obtained.

[0060] The prepared 3D gradient current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the lithium-philic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. 2 At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0061] Example 6

[0062] The LiFePO4 positive electrode was prepared by the method of Comparative Example 2, the 3D gradient current collector with pre-deposited lithium (5 mAh) in Example 5 was used as the negative electrode, celgard 2325 was used as the separator, and a 1 mol / L LiPF6 EC+DMC (volume ratio of 1:1) solution was used as the electrolyte to assemble a CR2016 button cell, and the cycle performance charge and discharge test was carried out at a rate of 0.5C.

[0063] Example 7

[0064] Place nickel foam (porosity 80%, thickness 50μm) in an MLD reactor, the reaction temperature is 400℃, the reaction time is 20min, and an upper organic layer with a thickness of 40nm is obtained. The material of the organic layer is polyethylene glycol; place the above precursor in a sputtering chamber, the sputtering target is a gold target, and the sputtering time is 60s; obtain a lower lithium-philic gold layer with a thickness of 60nm, and obtain a 3D gradient current collector.

[0065] The prepared 3D gradient current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the lithium-philic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. 2 At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0066] Example 8

[0067] Place nickel foam (porosity 80%, thickness 50μm) in an MLD reactor, the reaction temperature is 400℃, the reaction time is 5min, and an upper organic layer with a thickness of 10nm is obtained. The material of the organic layer is polyethylene glycol; place the above precursor in a sputtering chamber, the sputtering target is a gold target, and the sputtering time is 100s; obtain a lower lithium-philic gold layer with a thickness of 100nm, and obtain a 3D gradient current collector.

[0068] The prepared 3D gradient current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the lithium-philic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. 2 At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0069] Example 9

[0070] Place nickel foam (porosity 80%, thickness 50μm) in an MLD reactor, the reaction temperature is 400℃, the reaction time is 20min, and an upper organic layer with a thickness of 40nm is obtained. The material of the organic layer is polyethylene glycol; place the above precursor in a sputtering chamber, the sputtering target is a gold target, and the sputtering time is 150s; obtain a lower lithium-philic gold layer with a thickness of 150nm, and obtain a 3D gradient current collector.

[0071] The prepared 3D gradient current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the lithium-philic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. 2 At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0072] Example 10

[0073] Place nickel foam (porosity 80%, thickness 50μm) in an MLD reactor, the reaction temperature is 400℃, the reaction time is 50min, and an upper organic layer with a thickness of 100nm is obtained. The material of the organic layer is polyethylene glycol; place the above precursor in a sputtering chamber, the sputtering target is a gold target, and the sputtering time is 30s; obtain a lower lithium-philic gold layer with a thickness of 30nm, and obtain a 3D gradient current collector.

[0074] The prepared 3D gradient current collector was cut into discs with a diameter of 19 mm, and 5 mAh of metallic lithium was uniformly deposited on the lithium-philic side of the current collector in advance, and a lithium|current collector battery was assembled according to the method of Comparative Example 1. 2At a current density of 1 mAh / cm 2 Carry out a deposition-dissolution cycle.

[0075] Table 1. Membrane characteristics and cycle performance of each embodiment and comparative example

[0076]

[0077]

[0078] It can be seen from Table 1 that compared with the 2D current collector copper foil (250h) of Comparative Example 1, the 3D current collector with a high specific surface area improves the cycle life of the battery (>250h). It can be seen from Comparative Examples 3, 5 and Examples 1, 3 that reacting an organic layer on the surface will increase the electrochemical deposition overpotential (>33mV), and it increases with the increase in the thickness of the organic layer. For example, the thickness of the organic layer in Comparative Example 8 is 200nm, and the voltage reaches 200mV. However, since the lithium-philic layer is located in the lower layer, it has little effect on the deposition potential. It can be seen from Comparative Example 4 and Examples 1, 3, 10 (the thickness of the lithium-philic layer is controlled to be 30nm) that appropriately increasing the thickness of the organic layer can increase the cycle life of the battery. When the thickness of the organic layer is 80nm, the cycle life is the longest (600h); however, if the organic layer is too thick (reaching 100nm), the cycle life is reduced (530h). It can be seen from Comparative Example 5 and Examples 1, 7, and 9 (the thickness of the organic layer is controlled to be 40 nm) that the cycle life first increases and then decreases with the increase of the thickness of the lithium-philic layer; when the thickness of the lithium-philic layer is 80 nm, the cycle life can reach 650 h. In summary, an overly thick organic layer will hinder the transmission of lithium ions, and an overly thick lithium-philic layer will have too strong an interaction with metallic lithium, which is not conducive to the reversible deposition of lithium ions, resulting in a reduced cycle life. Therefore, it is necessary to optimize the organic layer and the lithium-philic layer in a suitable thickness range. Based on the above experiments, the organic layer thickness is selected to be 80 nm, the lithium-philic layer thickness is selected to be 60 nm, and the lithium battery cycle life can reach 800 h. This is because increasing the thickness of the metal layer can increase the lithium nucleation sites and promote the directional deposition of lithium; and the organic layer can effectively alleviate the volume expansion during the dissolution of lithium deposition, and prevent lithium dendrites from piercing the diaphragm and causing battery short circuit, thereby extending the battery cycle life.

[0079] Figure 2 It can be seen that the 3D gradient current collector prepared by the present invention can significantly improve the stability of metal lithium deposition and dissolution, and obtain a smaller deposition and dissolution overpotential. The composite 3D current collector is applied to LiFePO4|Li batteries, which can effectively improve the cycle performance of the battery, and the capacity retention rate is high after 200 cycles at a 0.5C rate.

[0080] from Figure 3It can be seen that the rate performance of the 3D gradient current collector has excellent performance, and Example 6 (organic layer thickness is 80nm, lithium affinity layer thickness is 60nm) has the best performance. This is because the high specific surface area can reduce the effective current density, and the lithium deposition is more uniform and dense. The 2D current collector has a small specific surface area, and it is easy to cause a tip effect due to surface unevenness, resulting in more uneven lithium deposition, which leads to poor rate performance.

[0081] Figure 4 It can be seen that compared with 2D current collector copper foil, the 3D current collector with high specific surface area can provide more active sites, and the lithium-philic interface can induce lithium nucleation, making the deposition more uniform and dense, thereby preventing lithium dendrites from piercing the separator and causing battery short circuit.

Claims

1. A 3D gradient current collector for a negative electrode of a lithium metal battery, the lithium metal battery comprising a separator, characterized in that: The current collector comprises a 3D conductive skeleton, which is a porous conductive material; one side of the 3D conductive skeleton is loaded with a lithium-phobic organic layer, and the other side thereof is loaded with a lithium-philic metal layer; wherein the side of the current collector loaded with the lithium-phobic organic layer faces the separator of the battery; the thickness of the lithium-phobic organic layer is 10-100 nm, and the thickness of the lithium-philic metal layer is 30-150 nm; The material of the organic layer is polyethylene glycol.

2. The 3D gradient current collector according to claim 1, characterized in that: The porous conductive material is one or more of foamed iron, foamed nickel, foamed copper, carbon felt, carbon cloth, and carbon paper; the material of the lithium-philic metal layer is one or more of gold, silver, platinum, and indium.

3. The 3D gradient current collector according to claim 1, characterized in that: The porous conductive material has a thickness of 10-100 μm and a porosity of 50-95%.

4. A method for preparing a 3D gradient current collector according to any one of claims 1 to 3, characterized in that: The lithium-phobic organic layer is prepared by molecular layer deposition, and the lithium-philic metal layer is prepared by sputtering.

5. The preparation method according to claim 4, comprising the steps of: (1) placing a porous conductive material in an MLD reactor, controlling the reaction temperature and time, and depositing a lithium-phobic organic layer on one side of the porous conductive material; (2) placing the porous conductive material after the organic layer is deposited in a sputtering chamber, controlling the sputtering time, and depositing a lithium-philic metal layer on the other side opposite to the lithium-phobic organic layer to obtain the current collector; The steps (1) and (2) are performed in no particular order.

6. The preparation method according to claim 5, characterized in that: The MLD reaction temperature is controlled at 300-500°C, the reaction time is controlled at 10-50min, and the sputtering control time is 20-200s.

7. Use of the 3D gradient current collector according to any one of claims 1 to 3 in a lithium metal battery.

Citation Information

Patent Citations

  • Three-dimensional composite current collector and preparation method thereof

    CN112670516A

  • Negative electrode composition material for lithium secondary battery and lithium secondary battery

    CN1757127A